2018
DOI: 10.1038/s10038-018-0413-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical validation of EHMT1 missense mutations in Kleefstra syndrome

Abstract: Kleefstra syndrome (KS) (9q34 deletion syndrome) is a rare autosomal dominant disorder characterized by intellectual disability, frequently coupled with a spectrum of complex physical and clinical manifestations. As the euchromatic histone methyltransferase-1 gene (EHMT1, GLP, or KMT1D) within the 9q34 region is deleted or mutated in most of the individuals with KS, its absence or defect in one allele is speculated to cause the major symptoms of the syndrome. Most of the EHMT1 mutations are frameshift or nonse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…A posteriori, the malformative picture of our patient fits well with that of Kleefstra syndrome. The biochemical characterization of this variant, made on the previously reported patient, demonstrated that it deteriorates the histone methyltransferase-1 gene activity (Yamada 2018). It is noteworthy that in our patient the detection of the variant in a chromatin-remodeling gene, prompted us to investigate whether C1M, although never reported in Kleefstra syndrome, were present, as indeed it was the case (Fig.…”
Section: W1 Histone Methyltransferasessupporting
confidence: 62%
“…A posteriori, the malformative picture of our patient fits well with that of Kleefstra syndrome. The biochemical characterization of this variant, made on the previously reported patient, demonstrated that it deteriorates the histone methyltransferase-1 gene activity (Yamada 2018). It is noteworthy that in our patient the detection of the variant in a chromatin-remodeling gene, prompted us to investigate whether C1M, although never reported in Kleefstra syndrome, were present, as indeed it was the case (Fig.…”
Section: W1 Histone Methyltransferasessupporting
confidence: 62%
“…A considerable strength of previously reported DNAm signatures is their utility in predicting the pathogenicity of variants of uncertain significance (VUS) [10,11,15] . Pathogenic missense variants are rare but present in KS [49] , Thus, we sought to assess the power/utility of the KS signature in classifying missense variants. We included one patient in the discovery group used to derive the DNAm signature, who carried a pathogenic missense variant, P809R, and therefore expected the KS DNAm signature to have clinical utility in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The EHMT1 gene encodes lysine methyltransferase, which can methylate histones. The lack of lysine methyltransferase impairs the proper control of the activity of certain genes in many body organs and tissues, leading to the developmental abnormalities and functional characteristics of KS ( Yamada et al , 2018 ). So far, most of the KS cases reported in the literature involve submicroscopic deletion of 9q34.3, but with the development of genetic testing technology, we can detect more intragenic pathogenic variant of EHMT1 gene responsible for KS, both result in haploinsufficiency of the EHMT1 gene.…”
Section: Discussionmentioning
confidence: 99%